The Impact of Misalignment of Organizational Structure and Product Architecture on Quality in Complex Product Development - Gokpinar, Bilal; Hopp, Wallace J.; Iravani, Seyed M. R. (Management Science, 2010)
Product architecture and organizational communication play significant roles in complex product development efforts. By using networks to characterize both product structure and communication patterns, we examine the impact of mismatches between these on new product development (NPD) performance. Specifically, we study the vehicle development process of a major auto company and use vehicle quality (warranty repairs) as our NPD performance metric. Our empirical results indicate that centrality in a product architecture network is related to quality according to an inverted-U relationship, which suggests that vehicle subsystems of intermediate complexity exhibit abnormally high levels of quality problems. To identify specific subsystems in danger of excessive quality problems, we characterize mismatches between product architecture and organizational structure by defining a new metric, called coordination deficit, and show that it is positively associated with quality problems. These results deepen our understanding of the impact of organizational structure and product architecture on the NPD process and provide tools with which managers can diagnose and improve their NPD systems.